Ageing induces tissue‐specific transcriptomic changes in Caenorhabditis elegans. (7th March 2022) - Wang, Xueqing; Jiang, Quanlong; Song, Yuanyuan; He, Zhidong; Zhang, Hongdao; Song, Mengjiao; Zhang, Xiaona; Dai, Yumin; Karalay, Oezlem; Dieterich, Christoph; Antebi, Adam; Wu, Ligang; et al.
Abstract: Ageing is a complex process with common and distinct features across tissues. Unveiling the underlying processes driving ageing in individual tissues is indispensable to decipher the mechanisms of organismal longevity. Caenorhabditis elegans is a well‐established model organism that has spearheaded ageing research with the discovery of numerous genetic pathways controlling its lifespan. However, it remains challenging to dissect the ageing of worm tissues due to the limited description of tissue pathology and access to tissue‐specific molecular changes during ageing. In this study, we isolated cells from five major tissues in young and old worms and profiled the age‐induced transcriptomic changes within these tissues. We observed a striking diversity of ageing across tissues and identified different sets of longevity regulators therein. In addition, we found novel tissue‐specific factors, including irx‐1 and myrf‐2, which control the integrity of the intestinal barrier and sarcomere structure during ageing respectively. This study demonstrates the complexity of ageing across worm tissues and highlights the power of tissue‐specific transcriptomic profiling during ageing, which can serve as a resource to the field. Synopsis: Whether organismal ageing is associated with specific changes in different tissues and organs remains poorly addressed. Here, dissection and transcriptomic analyses of diverse C. elegans tissues provides insight into the disting ageing trajectories and regulators in each of them. Five major somatic tissues—nervous system, hypodermis, intestine, coelomocyte and body all muscle ‐ undergo distinct transcriptomic changes during C. elegans ageing. Tissue‐specific changes between young and old worms are more pronounced than common changes in different tissues. Ageing regulates similar biological processes with different gene sets and regulators across tissues. Transcription factors irx‐1 /IRX and myrf‐2 /MYRF control ageing of intestine and body wall muscle, respectively. Abstract : Expression profiling of worm ageing uncovers common and organ‐specific molecular pathways involved in health deterioration.